Towards an African Christian ethics for the technological age : William Schweiker's Christian ethics of responsibility in dialogue with African ethics - De Villiers, D.E. (Dawid Etienne) (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.